Fruits and their phytochemicals in mitigating the ill effects of ionizing radiation: review on the existing scientific evidence and way forward. Issue 3 (23rd January 2023) - Raghu, Shamprasad Varija; Rao, Suresh; Kini, Venkataramana; Kudva, Avinash Kundadka; George, Thomas; Baliga, Manjeshwar Shrinath
Abstract : Although helpful in treating cancer, exposure to ionizing radiation can sometimes cause severe side effects, negating its benefit. Abstract : Although helpful in treating cancer, exposure to ionizing radiation can sometimes cause severe side effects, negating its benefit. In addition to its use in clinics, a nontoxic radioprotective agent can also be beneficial in occupational settings where humans are occupationally exposed for prolonged periods to low doses of radiation. Scientific studies using laboratory animals have shown that the fruits Aegle marmelos, Capsicum annuum, Citrus aurantium, Citrullus lanatus, Crataegus microphylla, Eugenia jambolana, Emblica officinalis, Garcinia kola, Grewia asiatica, Hippophae rhamnoides, Malus baccata, Malpighia glabra or Malpighia emarginata, Mangifera indica, Prunus domestica, Prunus avium, Prunus armeniaca, Psoralea corylifolia, Punica granatum, Solanum lycopersicum, Terminalia chebula, Vaccinium macrocarpon, Vitis vinifera and Xylopia aethiopica, and the phytochemicals gallic acid, ellagic acid, quercetin, geraniin, corilagin, ascorbic acid, hesperetin, ursolic acid, lycopene, naringin, hesperidin, rutin, resveratrol, β-sitosterol, apigenin, luteolin, chlorogenic acid, caffeic acid, mangiferin, diosmin, ferulic acid, and kaempferol are effective in preventing radiation-induced ill effects. Clinical studies with Emblica officinalis and Punica granatum have also shown that fruits help mitigate radiation-induced mucositis, dermatitis, and cystitis. For the first time, the current review summarizes the beneficial effects of fruits and phytochemicals in mitigating radiation-induced damage, the underlying mechanisms and the existing lacunae for future studies to be undertaken for the benefit of humans and the nutraceutical and agri-based industries.